A larger role for the regional development banks - Thomas Kampffmeyer (Deutsches Institut für Entwicklungspolitik (DIE), 2000)
With their 43 % share of total lendings by the multilateral development bank system (1994-1998), the African, Asian and Latin American development banks have become heavyweights in regional development financing. They were established to exploit regional specialization advantages, but have so far been only partly successful in this respect. In various areas they also continue to lag behind the World Bank in innovation and efficiency. In the debate on their future role the regional banks have established long-term strategies in response to growing private capital inflows, globalization and new challenges to development cooperation. To solve the overriding problem of the parallel structures of the World Bank and regional banks, the leading actors are now looking to increasingly radical approaches: a) de facto fusion through comprehensive harmonization, coordination and cooperation, the option favoured by the banks themselves, b) delinking through the regional banks' general withdrawal to complementary niche functions and c) the World Bank's withdrawal first from Asia and Latin America and later from Africa, as proposed in the Meltzer report.Despite a number of advantages, all three options are, on the whole, suboptimal because they essentially amount to replacing the cost and inefficiencies of overlapping with the cost of monopolistic structures. A more promising approach would consist in applying the competition principle and using the existing parallel structures to make the development bank system more dynamic. Within an efficient framework for regulating competition parallel structures are, after all, less a cost factor than a requirement for improved resource allocation, a driving force for conceptual and operational innovations and the basis for diversity and choice. A regulatory framework of this kind should make competition possible where it is superior to an administered division of labour as a means of allocating development cooperation resources and prevent competition where the aim is harmonization and coordination in the interests of low transaction costs; it should also ensure that both the development banks – through the abolition of the preferred creditor status as a general principle, for example – and the developing countries assume responsibility for the risks associated with lending. Finally, it should optimize the interface with private capital suppliers by applying the principle of subsidiarity and ensure that the development banks act as catalysts of private funding by taking a dynamic view of this principle. The better partner countries and regional banks responded to market requirements, the more efficient a regulatory framework would be.If they are to operate successfully in a competition-oriented development bank system, the regional banks must actively improve their core skills in the areas in which they derive comparative advantages from being close to regional realities. This is particularly true of the following priority areas: regional cooperation and integration, governance and regional crisis and conflict management.In giving itself a more distinct profile in the regional banks and in its collaboration with them, German government development cooperation should also focus on these areas, which are consistent with its strategic priorities or comparative advantages. It should also commit itself to reinforcing the principle of competition in the development bank system and so launch a process of rethinking in the bodies concerned. In addition, it should help to improve the regional banks' competitiveness by supporting the decentralization efforts, for example. It might also do more to seize the opportunities to acquire a more distinct development policy profile through earmarked trust funds, special facilities for training schemes, for example, and other such options as research consortia.
Keywords: 330